Health Worker Perspectives on Hospital Governance and Provision of Quality Spinal Injury Health Services at National Referral Spinal Injury Hospital in Kenya - Vundi , Susan Mule; Mwangi , Eunice Muthoni; Njoroge, Kezia (International Journal of Professional Practice, 2023)
Quality healthcare is a basic human right. It is a product of mutual interaction between the patient, healthcare provider and the environment of care. Quality of services delivered is often compromised due to delays which are costly to the patients and the facility. The study sought to evaluate how hospital governance influence provision of quality spinal injury health services at National tertiary public hospital in Kenya. Specifically, the study determined the influence of shared vision, responsiveness, and accountability on provision of quality health services. This was a cross sectional study guided by Donabedian model of care. A census was done on 80 clinical health workers. Data was collected using a structured questionnaire. A response rate of 78 (97.5%) was attained. Male respondents were 29 (37%), and female 49 (63%). Majority of the respondents were between (36-45) years; 36 (46%) were degree holders, and 29 (37%) diploma holders. Bivariate analysis showed that shared vision, responsiveness, and faccountability positively and significantly influenced provision of quality health services. This study recommends that, health facility management should implement governance structures, communicate the facility’s vision, nurture, and support accountability.